Temporal evolution of the lower hybrid cavities in the ionosphere plasma due to turbulent diffusion - Azarenkov, N.A.; Chibisov, D.V.; Kovalenko, N.I.; Maslennikov, D.I. (Вопросы атомной науки и техники, 2019)
The problem of evolution and disappearance of the lower hybrid cavities that are observed in the plasma of the Earth’s ionosphere is solved. It is assumed that the destruction of the cavity is caused by turbulent diffusion of plasma, which arises due to the drift instability of radially inhomogeneous plasma. The initial plasma density distribution on the radius in the cavity is considered to be the inverse Gaussian distribution. A solution of the diffusion equation is obtained, which at any time determines the radial dependence of the plasma density in the cavity. In the asymptotic limit t →∞ the plasma density in the cavity becomes equal to the density of the surrounding plasma.